Tectonostratigraphy of Middle and Upper Palaeozoic black shales from the Porto-Tomar-Ferreira do Alentejo shear zone (W Portugal): new perspectives on the Iberian Massif - Chaminé, H. I. (2003)
Middle/late Devonian and early Carboniferous metasedimentary sequences in the northernmost region (Porto-Espinho-Tomar) of the Ossa-Morena Zone (Portuguese Iberian Variscan Massif) contain black shales of very low to low-grade metamorphism. These metasedimentary rocks form a discrete NNW-SSE structure within a major shear zone (Porto-Tomar-Ferreira do Alentejo) and remain subparallel to the observed regional major structures (folding, thrusts or overthrusts). These black shales are overhanged and then imbricated in an upper Proterozoic metamorphic substratum. A multi-disciplinary study of these metasedimentary rocks from the Espinho-Tomar region has tectonostratigraphy, palynology, organic petrology and clay mineralogy combined methods. This approach provides new insights into the tectonic evolution and geological framework of Palaeozoic basement of the Iberian Variscides. Palaeoenvironmental and tectonostratigraphic implications on the Iberian geodynamic framework are discussed.